HUSBAND'S SUPPORT IN WIFE'S ANC IN EASTERN INDONESIA: DO REGIONAL DISPARITIES EXIST? - Agung Dwi Laksono; Ratna Dwi Wulandari; Nikmatur Rohmah; Ratu Matahari (Universitas Airlangga, 2022)
Background: Previous research has found that husband support can increase the participation of the wife's antenatal care (ANC) to prevent an increase in maternal mortality. Meanwhile, in the eastern region, the effort to provide pregnant women's health services tends to be lower than in Indonesia's other areas. Aims: The study analyzed regional disparities of husbands' support in wives' ANC in eastern Indonesia. Methods: Secondary data from the 2017 Indonesian Demographic and Health Survey were used in the study. In eastern Indonesia, the analytic units were wives aged 15 to 49, married, and pregnant in the previous five years. The study analyzed 2,005 respondents as a sample. In addition to the husband's support, the study examined region (province), residence, age, education, occupation, wealth, and parity as the independent variable. In the final stage, the study used a binary logistic regression test. Results: A husband in East Nusa Tenggara has 1.556 times the probability of a husband in Papua for a support wife's ANC (95% CI 1.082-2.237). Maluku husbands are 0.528 times less likely to support their wife's ANC than Papua husbands (95% CI 0.363-0.768). North Maluku husbands are 0.476 times less likely than Papua husbands to support their wife's ANC (95% CI 0.320-0.709). Meanwhile, there was no significant difference in the husband's support between West Papua and Papua. Conclusion: Regional disparities of husband's support in wife's ANC existed in eastern Indonesia.